The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/biomedicines11041120
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Type 1 Diabetes Mellitus, TNF-α, and IL-10 Gene Expression

Abstract: Type 1 diabetes mellitus (T1DM) is one of the major chronic diseases in children worldwide. This study aimed to investigate interleukin-10 (IL-10) gene expression and tumor necrosis factor-alpha (TNF-α) in T1DM. A total of 107 patients were included, 15 were T1DM in ketoacidosis, 30 patients had T1DM and HbA1c ≥ 8%; 32 patients had T1DM and presented HbA1c < 8%; and 30 were controls. The expression of peripheral blood mononuclear cells was performed using the reverse transcriptase–polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Previous study has found that the expression of TNF‐ α is negatively correlated with bone integration, while the expression of IL‐10 plays a positive role in bone integration. [ 36 ] Moreover, IL‐1β, well‐known for its capacity to incite pro‐inflammatory immune responses, carries the potential to disrupt cellular function and viability, thereby impeding tissue healing processes. [ 37 ] Moreover, NLRP3 has been implicated in promoting the development of diabetes and its complications.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has found that the expression of TNF‐ α is negatively correlated with bone integration, while the expression of IL‐10 plays a positive role in bone integration. [ 36 ] Moreover, IL‐1β, well‐known for its capacity to incite pro‐inflammatory immune responses, carries the potential to disrupt cellular function and viability, thereby impeding tissue healing processes. [ 37 ] Moreover, NLRP3 has been implicated in promoting the development of diabetes and its complications.…”
Section: Resultsmentioning
confidence: 99%
“…The role of cytokines in the pathophysiology of T1D is complex and not fully understood. Recent studies suggest that cytokines play an important role in the pathogenesis of the disease [ 21 , 30 , 31 , 32 ]. Most of the studied inflammatory markers have been shown to change gradually over time [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that plasma TNF-α levels were significantly higher in diabetic patients than in healthy subjects. Additionally, TNF-α levels positively correlated with age [ 31 ]. Available data on the relationship between TNF-α and glycemic control in type 1 diabetes are somewhat conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations